The relationship between attitudes and porn viewing activities with pre-marital sexual behavior in adolescents - Hastuti, Puji; Muftia, Nabila Rurotul; Nurlela, Lela (Pediomaternal Nursing Journal, 2024)
Introduction: The widespread availability of the internet, coupled with adolescents' natural curiosity about sexuality, has created avenues for accessing pornographic websites. However, this curiosity, when not tempered with self-restraint, can lead adolescents into the habit of watching pornographic films. One significant consequence of engaging in this behavior is its potential to influence pre-marital sexual activity among adolescents. This study aimed to investigate the correlation between attitudes toward and the frequency of watching pornographic movies and pre-marital sexual behavior among adolescents in Sidoarjo.Methods: The study employed a descriptive analytics approach with a cross-sectional design. A sample of 138 adolescents was selected using probability sampling, specifically the cluster simple random sampling method. Two research instruments were utilized: the Cyber Pornography Use Inventory (CPUI) for gathering data on porn-watching activity and the Adolescent Sexual Activity Index (ASAI) for collecting information on sexual behavior. The data were then analyzed using the Spearman rank correlation method.Results: The findings indicated that the majority of students in Sidoarjo exhibited a non-supportive attitude category (48.6%, n= 67), with low engagement in watching porn movies (44.2%, n= 61), and most teenagers demonstrated low/less risky sexual behavior (63%, n= 87). Moreover, the results revealed significant relationships between attitudes and sexual behavior (P-value <0.001) as well as between watching porn and sexual behavior (P-value <0.001).Conclusions: This research suggests the importance of parental and teacher involvement in guiding and supervising adolescents to prevent engagement in risky behaviors such as watching pornography and engaging in pre-marital sexual activity. By actively monitoring their children and providing guidance, parents and teachers can play a crucial role in minimizing such behaviors and promoting adolescent reproductive health through counseling and education. Keywords: adolescent; attitude; porn-watching activity; pre-marital sex